Aberrant expression of BCL11B in mycosis fungoides and its potential role in interferon‐induced apoptosis. Issue 8 (19th May 2013) - Gu, Xiaoguang; Wang, Yang; Zhang, Gaolei; Li, Weiwei; Tu, Ping
Abstract: BCL11B is a Kruppel‐like C2H2‐type zinc finger transcription factor, which has been associated with several human malignancies. Recent evidence showed that overexpressed BCL11B conferred chemoresistance to malignant T cells and that inhibiting BCL11B led to increased apoptosis, suggesting its potential pathogenic relevance in cutaneous T‐cell lymphomas (CTCL), which were characterized by the resistance to chemotherapy‐induced apoptosis. To investigate the expression pattern of BCL11B in different stages of mycosis fungoides (MF), quantitative reverse transcription polymerase chain reaction and immunohistochemistry were performed to compare the mRNA and protein expression among different stages of MF and benign inflammatory dermatoses (BID), respectively. BCL11B demonstrated significant upregulation in all stages of MF, compared with BID, in both mRNA expression level and protein level. In addition, BCL11B expression increased with advancing lesion tumor stage and overall disease stage. Further, to evaluate the dynamic expression of BCL11B under CTCL‐directed treatment, BCL11B expression and cell apoptosis were evaluated after interferon (IFN)‐α‐2b and methotrexate treatment on CTCL cell line Hut78 cells. IFN‐α‐2b, but not methotrexate, induced BCL11B inhibition and cell apoptosis, suggesting that BCL11B may play important roles in the anti‐CTCL effect of IFN‐α‐2b. In conclusion, our study demonstrated the overexpression of BCL11B in MF lesions and its potential relevance to disease progression. In addition, we provided evidence for BCL11B inhibitory approaches as a potential treatment to target chemoresistant tumor cells in advanced MF.